A Highly Sensitive Hydrogen Peroxide Biosensor Based on Hemoglobin Immobilized on Cadmium Sulfide Quantum Dots/Chitosan Composite Modified Glassy Carbon Electrode. Issue 11 (2nd October 2014) - Butwong, Nutthaya; Zhou, Lin; Moore, Eric; Srijaranai, Supalax; Luong, John H. T.; Glennon, Jeremy D.; Aggarwal, Suresh K.
Abstract An L‐cysteine capped cadmium sulfide‐chitosan nanocomposite has been synthesized, characterized and used for surface modification of a glassy carbon electrode. With direct electron transfer, hemoglobin (Hb) adsorbed strongly on the nanocomposite and displayed excellent bioelectrocatalysis for H2O2. The biosensor was capable of reducing H2O2 at −0.35 V, with a detection limit of 3.13 nM, linearity in the range of 15 nM to 10 µM and a response time of less than 2 s. The MichaelisMenten constant (KM) was 0.57 nM, attesting high bioelectrocatalysis of immobilized Hb for H2O2. Reproducibility of the fabrication method was very satisfactory with a relative standard deviation of 5.3 %. The biosensor lost only 6.5 % of its original response after 7 days when stored in a pH 7.4 PBS at 4 °C.